A PANORAMA OF BRAZILIAN ACADEMIC RESEARCH ON HIGH ABILITIES/GIFTEDNESS FROM 2020 TO 2024 - Araujo dos Santos, Willians; Gomes, Vitor (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to present an overview of postgraduate research on High Abilities/Giftedness (HA/G) in Brazil during the period from 2020 to 2024. To this end, a search was conducted in the Brazilian Digital Library of Theses and Dissertations (BDTD), through which 80 (eighty) studies were identified and examined. The discussion considered the volume of research, the fields of knowledge engaged with the topic, and the main themes addressed. The study reveals a growing, albeit uneven, attention to the subject within the Brazilian educational context and points to the need for greater investment in public policies, professional training, and the expansion of the areas of knowledge involved. Thus, it is concluded that further theoretical and practical development of research on HA/G is essential to ensure an inclusive education that is responsive to the singularities of this population.